Exploring Push and Pull Factors Influencing Students' Decisions to Study Tourism and Hospitality Management: A Bangladeshi Perspective - Sukrana, Bipasha (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: The tourism and hospitality industry in Bangladesh is experiencing rapid growth and creating a strong demand for skilled professionals. However, little is known about why students choose to study this subject. This study aims to identify the push and pull factors that influence Bangladeshi students' decisions to pursue higher education in Tourism and Hospitality Management. Methods: Data were collected through a structured questionnaire from undergraduate students studying Tourism and Hospitality Management at several universities in Bangladesh. A total of 312 valid responses were analyzed using multiple regression analysis with SPSS software to determine the factors influencing students’ academic choices. Results: The regression model explains a substantial proportion of variance in students' academic decisions (Adjusted R² = 0.840). Work opportunities while studying emerged as the strongest predictor (? = 0.397, p < 0.001), followed by opportunities to go abroad and global career aspirations. In contrast, intrinsic career interest played a statistically insignificant role. Conclusion: The findings indicate that pragmatic and career-oriented considerations dominate students' decisions to pursue tourism and hospitality education in Bangladesh, highlighting the importance of employment-related factors over intrinsic motivation. Limitations: The study used a relatively small sample drawn from selected universities, which may limit the generalizability of the findings to all tourism and hospitality students in Bangladesh. Contribution: This research contributes to the limited empirical literature on tourism and hospitality education in developing countries by providing quantitative evidence based on multiple linear regression analysis. It offers practical insights for educators, policymakers, and industry stakeholders to better align academic programs with students' motivations and labor market demands.